Improving Students’ Speaking Ability through Morning English Program Extracurricular Activities in Indonesia - Anshori, Mohammad Isya (Educational Challenges, 2023)
This study aim was to describe the activities of the Morning English Program (MEP) and their impact on improving students’ speaking skills. This study used a qualitative descriptive research method. To collect the data, the researchers of the administered questionnaire were divided into two groups: an English teacher in Indonesia at SMK Bhakti Mulia Pare and 44 of 1the 11th grade students who became members of the MEP. Then, the researcher interviewed five students and one teacher to expand the information received. Data analysis carried out was collecting data, displaying data, and drawing conclusions. The reliability of the study data was checked through data triangulation. The results of1this study identified the MEP activities consisted of speaking, reading aloud, telling stories and group discussions. Following the implementation of these activities, students’ speaking skills which include grammatical accuracy, pronunciation skills, vocabulary mastery, fluency, and the ability to organize concepts while speaking. In addition, students experienced lower anxiety and increased interest in learning English. This positive impact enhances the teacher’s role in using appropriate teaching methods and creating a positive learning environment. Conclusion. Henceforth, this study illustrates the importance of planning before implementing an English program and adopting similar activities to improve students’ speaking skills.